2016
DOI: 10.1590/1678-98652016000300001
|View full text |Cite
|
Sign up to set email alerts
|

Decreased calorie and protein intake is a risk factor for infection and prolonged length of stay in surgical patients: A prospective cohort study

Abstract: Objective The aim was to assess whether postoperative calorie and protein intakes increase the risk of infection and prolonged length of stay in a tertiary care university hospital in Southern Brazil. Methods This is a prospective cohort study approved by the hospital's Research Ethics Committee. The sample consisted of adult patients undergoing elective surgery. The exclusion criteria included patients who could not undergo nutritional assessment and those with a planned hospital stay of fewer than 72 hours. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
3
2
2
Order By: Relevance
“…The scarcity of studies highlights that not much has been researched regarding ICI in SSA and the need to conduct more research on this area in the region. However, studies in Malaysia and Brazil reported a very high proportion (more than 60%) of ICI (2,20) compared to our study. This difference might be due to methodological variations such as a smaller sample size used by the study in Malaysia and different inclusion criteria used in Brazil.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The scarcity of studies highlights that not much has been researched regarding ICI in SSA and the need to conduct more research on this area in the region. However, studies in Malaysia and Brazil reported a very high proportion (more than 60%) of ICI (2,20) compared to our study. This difference might be due to methodological variations such as a smaller sample size used by the study in Malaysia and different inclusion criteria used in Brazil.…”
Section: Discussioncontrasting
confidence: 84%
“…Although there is a lack of consensus on the clinical manifestations or markers of reduced calories consumption in patients, evidence from certain studies shows that people can have symptoms like hunger, fatigue, dry mouth, bowel irregularity, head and neck pain, nausea, and hair loss (16)(17)(18). This remains unclear, unless calories intake is screened using valid nutrition assessment methods, (2,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Quanto à ingestão proteica, não houve em nosso trabalho associação entre o BP e o tempo de internação ou complicações pós-operatórias. Foi observado, em um estudo anterior com pacientes cirúrgicos, importante inadequação do consumo energético e descritas associações com o aumento de infecções e maior tempo de internação 18 . Além disso, outro trabalho realizado com pacientes submetidos a gastrectomia sleeve evidenciou maior perda de massa magra e consequências associadas nos pacientes com significativa inadequação proteica 19 .…”
Section: Discussionunclassified
“…Contudo, a divisão das representações gráficas em quartis objetivou evitar vieses de subjetividade e já foram utilizadas por outros autores 11,24 . Com relação à ASG 25 , o método de avaliação nutricional utilizado nosso estudo, pode-se citar que este instrumento depende da memória do entrevistado, com relação a algumas perguntas.…”
Section: Discussionunclassified